The Lost Generation in Europe? - the Economic Crisis and Starting a Family - Sandra Schaffner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Young adults are the most hit by the current economic crisis. This can be observed in high youth unemployment rates in countries like Spain. At the same time fertility is relatively low in the most concerned countries whereas those in their fertile phase experience high unemployment rates. Based on these facts we investigate how marriage and fertility decisions in Europe respond to economic insecurity. We analyse both, the individual economic status as well as increased insecurity due to increased risk of unemployment during the financial crisis. Our results reveal that employed workers are the most likely to marry. However, this relationship becomes smaller during the economic crisis. Men in the most struck countries are even less likely to marry when they are unemployed during recession. Although we find effects on marriage we cannot observe any effects of the economic crisis on fatherhood. Over all countries we can observe that the fertility rate of employed women becomes higher during the economic crisis. Especially unemployed and self employed women in Greece, Italy and Cyprus are less fertile.
Keywords: J12; J13; J64; 330